Causality Relationship between Tourism, Foreign Direct Investment and Economic Growth in Taiwan - Yu-Chi, Sung; Lin, Hung-Pin (Asian Journal of Economic Modelling, 2018)
This study attempts to investigate the existence of Granger causality and cointegrated relationships among international tourist arrivals (ITA), foreign exchange income (FEI), foreign direct investment (FDI), and economic growth (GDP) using Taiwan’s tourism data from 1976 to 2016. The cointegrated results confirm the existence of long-run relationships among the variables, and the Granger causality results show that there is a bi-directional causality between GDP and ITA. In addition, there is a unidirectional causality running from one to another in each pair of these variables, while there is no causality between ITA and FDI. Based on such causality evidence, policy implications reveal that to promote GDP, paying attention to FDI to expand ITA is a feasible policy to achieve economic growth.